A Family of Coverage Testing Criteria for Coloured Petri Nets - Simão, Adenilso da Silva; Souza, Simone do R. S. de; Maldonado, José Carlos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2003)
In this paper, we propose a family of specification-based coverage testing criteria for Coloured Petri Nets (CPNs). CPNs are an extension of Petri Nets with the capability of expressing, defining and handling datatypes and structured values. The main approaches used for testing and validation of CPNs based on specifications are simulation and analysis of properties. However, these approaches do not essentially provide a mechanism for quantifying the testing activity, compromising the testing quality assessment. The coverage criteria family proposed in this paper aims at complementing this scenario by providing mechanisms either to evaluate the adequacy of test sequences (e.g., sequences generated by simulation) or to guide the generation of adequate test sequences with respect to a given criterion. The underlying model to derive the requirements of the testing criteria is the occurrence graph. The concepts and criteria presented in this paper are supported by a prototyping tool. Some examples are provided to illustrate the main ideas.